Primary angioplasty versus thrombolysis for acute ST-elevation myocardial infarction: an economic analysis of the National Infarct Angioplasty project. Issue 9 (8th June 2009) - Wailoo, Allan; Goodacre, Steve; Sampson, Fiona; Alava, Mónica Hernández; Asseburg, Christian; Palmer, Stephen; Sculpher, Mark; Abrams, Keith; de Belder, Mark; Gray, Huon
Abstract : Objective: To estimate the cost-effectiveness of primary angioplasty compared with thrombolysis for acute ST elevation myocardial infarction. Design: Cost analysis of UK observational database, incorporated into decision analytical model. Methods: Patients receiving treatment within a comprehensive angioplasty service were compared with control patients receiving thrombolysis-based care. The treatment costs and delays to treatment of thrombolysis and angioplasty were estimated. These estimates were then incorporated into an existing model of cost-effectiveness that synthesises evidence from 22 randomised trials to estimate health outcomes measured by quality-adjusted life years (QALYs). Main outcome measures: Costs from a health service perspective and outcomes measured as quality adjusted. Results: The mean cost of the initial treatment was £3509 for thrombolysis at control sites, £5176 for angioplasty in usual working hours at National Infarct Angioplasty Project sites and an additional £245 if undertaken out of hours. Angioplasty-based care had an incremental cost of £4520 per QALY gained and 0.9 probability of being cost-effective at a threshold of £20 000 per QALY gained. This probability was >0.95 if patients were directly admitted to the cardiac catheter laboratory, 0.75 if admitted via the emergency department or coronary care unit and 0.38 if transferred to the angioplasty centre from another hospital. Conclusions: Overall, primary angioplasty-based care is highly likely to be cost-effective at an assumed threshold of £20 000 per QALY gained. It is more likely to be cost-effective if patients are admitted directly to the cardiac catheter laboratory rather than via other hospital departments, or if transferred from another hospital.